SINTESIS GEOPOLIMER DENGAN BAHAN DASAR KAOLIN CAPKALA SEBAGAI ADSORBEN ION Pb(II) DALAM LARUTAN (SYNTHESIS OF GEOPOLYMERS WITH BASE MATERIALS KAOLIN CAPKALA AS ADSORBENT ION Pb(II) IN SOLUTION) - Nur Ridha An Nisa; Intan Syahbanu; Winda Rahmalia; Nurlina Nurlina (Tanjungpura University, 2023)
Geopolymer synthesis was carried out using kaolin, for the adsorption of Pb (II) ions in solutions. Kaolin is used by Kaolin Capkala from Bengkayang Regency, West Kalimantan. This kaolin was first modified into metakaolin. The scaling up of geopolymers is carried out by making an activating solution, namely by mixing NaOH and Na2SiO3. The activating solution is mixed into metakaolin. The mass composition of each component in the geopolymer: metakaolin of 94,5 grams, Na2SiO3 of 57 grams, NaOH of 12 grams, and H2O of 30 grams. The formed geopolymers are tested for their adsorption ability against Pb(II) ions. The research results show the success of geopolymer formation as indicated by FTIR and XRD characterization results. Based on the FTIR results, several indications of successful geopolymer formation are seen in the shift and widening of the Si-O absorption peak at wave number 1109 cm-1 for kaolin to 1058 cm-1 for metakaolin and 1016 cm-1 for geopolymer; the appearance of O-C-O bond absorption in CO32- at 1362 cm-1 in geopolymer; and a shift in absorption of Al-O (Al (VI), wherein kaolin it is indicated by a wave number of 536 cm-1 while in metakaolin it is characterized by a wave number of 544 cm-1 and for geopolymer a wave number of 553 cm-1 indicates it. XRD diffractogram of the formation hump's appearance shows the amorphous characteristics of metakaolin and geopolymer at around 2θ 26o-35o. The application of geopolymer for Pb adsorption shows that Pb(II) can be adsorbed well in geopolymers with the maximum adsorption capacity of 2.77 mg/ g obtained at various concentrations of 40 ppm.